2020
DOI: 10.1186/s12879-020-05420-w
|View full text |Cite|
|
Sign up to set email alerts
|

Vogesella perlucida-induced bacteremia in an advanced-age patient: first case report

Abstract: Background Vogesella species are common aquatic, Gram-negative rod-shaped bacteria, originally described in 1997. Vogesella perlucida was first isolated from spring water in 2008. Furthermore, bacterial pathogenicity of Vogesella perlucida has never been reported. Here, we report the first case of rare Vogesella perlucida-induced bacteremia in an advanced-age patient with many basic diseases and history of dexamethasone abuse. Case presentation A 71-year-old female was admitted with inflamed upper and lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Recreational hot springs are known to harbor pathogens associated with human diseases such as Clostridium and Legionella strains (Chan et al 2015, Ghilamicael et al 2018. Our results suggested the occurrence of opportunistic pathogens causing bacteremia or the presence of bacteria in the human blood, such as Comamonas testosteroni (3.70%), Comamonas aquatica (3.54%), and Vogesella perlucida (0.59%) (Farooq et al 2017, Farshad et al 2012, Kaeuffer et al 2018, Tartar and Tartar 2020, Tiwari and Nanda 2019, Yu et al 2020. Furthermore, genus Blautia (3.21%) and Ruminococcus (2.86%), which are related to fecal contamination, were also observed (Devane et al 2020, Koskey et al 2014, Staley et al 2016).…”
Section: Discussionmentioning
confidence: 66%
“…Recreational hot springs are known to harbor pathogens associated with human diseases such as Clostridium and Legionella strains (Chan et al 2015, Ghilamicael et al 2018. Our results suggested the occurrence of opportunistic pathogens causing bacteremia or the presence of bacteria in the human blood, such as Comamonas testosteroni (3.70%), Comamonas aquatica (3.54%), and Vogesella perlucida (0.59%) (Farooq et al 2017, Farshad et al 2012, Kaeuffer et al 2018, Tartar and Tartar 2020, Tiwari and Nanda 2019, Yu et al 2020. Furthermore, genus Blautia (3.21%) and Ruminococcus (2.86%), which are related to fecal contamination, were also observed (Devane et al 2020, Koskey et al 2014, Staley et al 2016).…”
Section: Discussionmentioning
confidence: 66%
“…In a recent study, Yu et al, using a 16S rRNA gene sequence analysis, demonstrated that a Vogesella perlucida isolate was misidentified as H. alvei by traditional microbiological testing [ 97 ]. The H. alvei isolate exhibits colistin resistance, which is unusual for an environmental isolate.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several Vogesella species have been reported. Vogesella indigofera has been isolated from oxidation pond sediments, whereas others have been found in hot springs, river water, and in the rice rhizosphere, among others [2]. In addition, Vogesella urethralis has been isolated from the urine of a patient with chronic renal failure.…”
Section: Discussion Andmentioning
confidence: 99%
“…To date, only Vogesella perlucida has been reported as a pathogen in the genus Vogesella. However, Yu et al described a case of bacteremia in an elderly woman who had been taking dexamethasone for a long time, and bacteremia developed when she touched a pond snail with her wounded hand [2]. Vogesella, such as Pseudomonas, is assumed to cause opportunistic infections.…”
Section: Discussion Andmentioning
confidence: 99%
See 1 more Smart Citation